2010
DOI: 10.1007/s11105-010-0252-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Jasmonate Biosynthetic Gene Allene Oxide Cyclase in Artemisia annua L., Source of the Antimalarial Drug Artemisinin

Abstract: Artemisinin is currently the best therapeutic against both drug-resistant and cerebral-malaria-causing strains of Plasmodium falciparum. Allene oxide cyclase (AOC) is the key enzyme in the biosynthetic pathway of jasmonates. In this study, a full-length cDNA of AOC gene (named as AaAOC) was cloned from Artemisia annua L. AaAOC was 1,007 bp, containing an open reading frame (750 bp) encoding 249 amino acids. Comparative and bioinformatic analyses revealed that the deduced protein of AaAOC was highly homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In addition, the monocotyledonous AOCs from rice, L. mollis, wheat, barley, maize, and sorghum were clustered together in Group II. Four AtAOC proteins together with GhAOC1 were clustered in Group III and diverged earlier than other species (Figure 3), which is consistent with the previous reports [9,33].…”
Section: Phylogenetic and Structural Analyses Of Aoc Genes From Diffesupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the monocotyledonous AOCs from rice, L. mollis, wheat, barley, maize, and sorghum were clustered together in Group II. Four AtAOC proteins together with GhAOC1 were clustered in Group III and diverged earlier than other species (Figure 3), which is consistent with the previous reports [9,33].…”
Section: Phylogenetic and Structural Analyses Of Aoc Genes From Diffesupporting
confidence: 91%
“…To characterize ClAOC1 and ClAOC2, a multiple sequence alignment was performed for their full-length amino acid sequences, as well as other published AOC proteins, such as SlAOC from Solanum lycopersicum [6], HvAOC from Hordeum vulgare [13], HnAOC from Hyoscyamus niger [31], JcAOC from Jatropha curcas [32], AaAOC from Artemisia annua [33], OsAOC from Oryza sativa [12], LmAOC from Leymus mollis [34], TaAOC1 from Triticum aestivum [17], GhAOC1 from Gossypium hirsutum [8], GmAOC3 from Glycine max [18], CsAOC from Camellia sinensis [35], and Ljaoc1 from Lotus japonicus [10]. The results showed that the identity between ClAOC1 and ClAOC2 was 62.13%, and the amino acid sequences of ClAOC1 and ClAOC2 shared 58.05% to 69.08% identity with other AOC proteins ( Figure 2).…”
Section: Characterization Of Claoc1 and Claoc2mentioning
confidence: 99%
“…Therefore, tomato fruit of RNAi lines displayed deep red coloration compared to the control fruit during ripening (Sun et al, 2012). ABA treatment could also increase the production of artemisinin (Lu et al, 2011). The full-length cDNA of ABA receptor AaPYL9 was cloned and characterized from A. annua .…”
Section: Plant Metabolic Engineering Strategies For Production Of Phamentioning
confidence: 99%
“…MeJA, an important plant defense response signaling molecules, is extensively involved in the activation of plant defense-related genes (Turner et al 2002;Lu et al 2011). T. chinensis cells were treated with 100 μM MeJA; then, the mRNA accumulation of TcLOX1 and TcLOX2 was detected.…”
Section: Expression Analysis Of Tclox1 and Tclox2mentioning
confidence: 99%